This Time it Might be Different: Analysis of the Impact of Digitalization on the Labour Market - Lovergine, Saverio; Pellero, Alberto (European Scientific Journal, ESJ, 2018)
The acceleration of progress in the fields of robotics, artificial intelligence and new digital technologies are changing the economic "dogma" that technological development enhances wealth and life standard of a country. A recent literature on the possible consequences for employment deriving from the widespread use of such technologies, highlights that there are good reasons that this time, compared to previous industrial revolutions, may be different (Ford, 2015). This paper analyzes the future impact that the progress of robotics, AI and new digital technologies will have on the employment, tasks and skills of workers of industrialized countries.